Simultaneous Measurement Of 3-D Displacement Components Caused By Crack Growth Using Circular Gratings Moire Fringes And Graphical Analysis - Yen, Kin Sam (2012)
Cracking is well-known to be a major cause of failures in concrete structures. By monitoring the growth of cracks, early remedial measure can be taken to save the structure from failure. To sense all the three crack modes namely, opening mode, sliding mode and tearing mode, a method that is able to measure the 3-D displacement components simultaneously with a single setting is needed. The moiré pattern formed by overlapping two circular gratings with slightly different pitches is proposed as a measurement tool because the moiré pattern is repeatable and unique for a relative in-plane (2-D) displacement between the two gratings.